IMAJINASI SEBAGAI ROH KREATIF INTELEK DALAM PROSES KREASI PENCIPTAAN KARYA SENI - Susapto Murdowo (FBS UNY, 2007)
Many people write about art and works of art. The discussions about works of arts use new paradigms such as phenomenology, post-structuralism, semiotics as well as hermeneutics, to reveal the meanings of art and visual art. In the process of evaluating and analyzing works of art, some of the paradigms tend to pay no attention to the subject (the artist). This article is written to remind that an artist as the subject needs to be regarded as the centre of meanings as a whole, including the background that surrounds the art creating process.